OPRESI DAN KUASA ATAS TUBUH PEREMPUAN DALAM TRADISI MASYARAKAT BUDAYA (STUDI KASUS: SUNAT PEREMPUAN DI BANTEN) - Adinda Putri Kirana Lutfi (2023)
Female genital mutilation is generally based on the traditions and culture of the society, passed down from generation to generation, and strengthened through religious teachings. The implementation of female genital mutilation is very strongly related to sexual control and forms of power over women. This study aims to examine the form of oppression that occurs in women in cultural groups through a case study of female genital mutilation in Banten and its impact on the recognition of women's rights in indigenous peoples. Researchers use the political theoretical framework of recognition of cultural group identity and the concept of forms of oppression to analyze the research. The research paradigm used is postpositivism, with qualitative research methods and phenomenological approaches. The research location is in Kemuning Village, Kresek District, Tangerang Regency, Banten Province. The subjects of this study were women who experienced female genital mutilation. The data collection method uses in-depth interview techniques. Data analysis using the Interpretative Phenomenological Analysis (IPA) method. The results showed that there are two forms of oppression that occur in the practice of female genital mutilation in Banten, namely powerlessness and violence. This form of oppression is the impact of women's weakening in the practice of female genital mutilation which is one of the negative implications of the politics of recognition of cultural group identity in a country.